Respuestas
Respuesta dada por:
2
se usa la formula se la funcion que es
d/dx(u^n)= n(u^n-1)d/dx(u)
en este caso tu
u=1+x^2
y queda
2/3((1+2x)^2/3-1)d/dx(1+x^2)
2/3((1+x^2)^-1/3)(2x)
4x/3(1/(1+x^2)^1/3)
4x/3(1+x^2)^1/3
d/dx(u^n)= n(u^n-1)d/dx(u)
en este caso tu
u=1+x^2
y queda
2/3((1+2x)^2/3-1)d/dx(1+x^2)
2/3((1+x^2)^-1/3)(2x)
4x/3(1/(1+x^2)^1/3)
4x/3(1+x^2)^1/3
Respuesta dada por:
2
Seguimos las normas de derivación.
![d(y) =n* u^{n-1} *d(u) d(y) =n* u^{n-1} *d(u)](https://tex.z-dn.net/?f=d%28y%29+%3Dn%2A+u%5E%7Bn-1%7D+%2Ad%28u%29)
entonces
![f(x)= (1+x^2)^{ \frac{2}{3} } f(x)= (1+x^2)^{ \frac{2}{3} }](https://tex.z-dn.net/?f=f%28x%29%3D+%281%2Bx%5E2%29%5E%7B+%5Cfrac%7B2%7D%7B3%7D+%7D+)
![f'(x)= \frac{2}{3} ( 1+x^2)^{ \frac{2}{3}-1 } *(2x) f'(x)= \frac{2}{3} ( 1+x^2)^{ \frac{2}{3}-1 } *(2x)](https://tex.z-dn.net/?f=f%27%28x%29%3D+%5Cfrac%7B2%7D%7B3%7D+%28+1%2Bx%5E2%29%5E%7B+%5Cfrac%7B2%7D%7B3%7D-1+%7D+%2A%282x%29)
![f'(x)= \frac{2}{3} (1+x^2) ^{-1/3} *2x f'(x)= \frac{2}{3} (1+x^2) ^{-1/3} *2x](https://tex.z-dn.net/?f=f%27%28x%29%3D+%5Cfrac%7B2%7D%7B3%7D+%281%2Bx%5E2%29+%5E%7B-1%2F3%7D+%2A2x)
![f'(x) = \frac{2}{3 \sqrt[3]{1+ x^{2} } } *2x = \frac{4x}{3 \sqrt[3]{ x^{2} +1} } f'(x) = \frac{2}{3 \sqrt[3]{1+ x^{2} } } *2x = \frac{4x}{3 \sqrt[3]{ x^{2} +1} }](https://tex.z-dn.net/?f=f%27%28x%29+%3D++%5Cfrac%7B2%7D%7B3+%5Csqrt%5B3%5D%7B1%2B+x%5E%7B2%7D+%7D+%7D+%2A2x+%3D++%5Cfrac%7B4x%7D%7B3+%5Csqrt%5B3%5D%7B+x%5E%7B2%7D+%2B1%7D+%7D+)
entonces
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años